Comparing Pre and Post-Merger Performance of Bank Syariah Indonesia: A Maqashid Shariah Index Analysis - Inarawi, Wiwi; Djuwita, Diana; Wartoyo, Wartoyo; Wahyuningsih, Nining (Institut Agama Islam Negeri Kendari, 2024)
This study evaluates the performance impact of Indonesia's landmark Islamic bank merger by comparing pre and post-merger performance using the Maqashid Shariah Index (MSI) framework. The research analyzes performance data from the three merged banks - Bank Rakyat Indonesia Syariah (BRIS), Bank Negara Indonesia Syariah (BNIS), and Bank Syariah Mandiri (BSM) - for five years prior to their merger (2016-2020), and compares it with two years of post-merger data (2021-2022) from Bank Syariah Indonesia (BSI). Using a quantitative approach with descriptive verification methods, the study employs Simple Additive Weighting and Mann-Whitney U Test to analyze performance across three MSI dimensions: education of individuals (Tahzib al-Fard), establishment of justice (Iqamah al-Adl), and promotion of welfare (Jalb al-Maslahah). The findings reveal that among the pre-merger banks, BSM demonstrated the strongest overall MSI performance. Post-merger analysis shows that while BSI achieved performance stability in its first two years, its MSI score remains slightly below the pre-merger average. Statistical analysis using the Mann-Whitney U Test indicates no significant performance differences between pre and post-merger periods across all MSI dimensions. These results provide important insights for Islamic banking practitioners and regulators regarding the early performance outcomes of this strategic merger while highlighting opportunities for further optimization of BSI's adherence to Shariah objectives.